A rare case of lichen planus follicularis tumidus involving bilateral retroauricular areas - Vaishali H Wankhade; Pranita P Daware; Bhagyashree Babanrao Supekar; Rajesh Pratap Singh (Wolters Kluwer Medknow Publications, 2020)
Lichen planus follicularis tumidus (LPFT) is an extremely rare variant of lichen planus characterized by white to yellow milia-like cysts and comedones on a violaceous to hyperpigmented plaque most commonly involving retroauricular area. Clinically, it resembles milia en plaque. It is usually asymptomatic, more common in middle-aged females. Histopathologically, it has features of lichen planopilaris along with follicular cysts in dermis surrounded by lichenoid infiltrate. We are reporting a case of LPFT in a 62-year-old male patient involving bilateral retroauricular areas due to the rarity of this condition.